Intake and digestibility of some nutritional components of sorghum silage (Sorghum bicolor L. Moench) with or without additives in sheep - Correa, Rômulo Alexandre; Silva, Leandro das Dores Ferreira da; Bett, Vanderlei; Castro, Valdecir de Souza; Ribeiro, Edson Luis de Azambuja; Beran, Fernando Henrique Brussi; Rocha, Marco Antônio da; Ezequiel, Jane Maria Bertocco; Massaro Júnior, Fernando Luiz (Semina: Ciências Agrárias, 2007)
This trial was conducted to evaluate the average daily intake of sorghum silage, sorghum silage with corn meal as additive and sorghum silage with Lacto Silo as additive. It was also evaluated the apparent digestibility in vivo and using the acid detergent lignin (ADL) as marker. Values of apparent digestibility of some nutritive components of these tree silages were correlated. Nine castrated lambs, without defined race, with initial average body weight of 30.7 Kg were used, distributed in tree treatments and two periods. The animals were placed in metabolic cages and the sorghum silage without additive provided higher intake of dry matter (DM), organic matter (OM), acid detergent fiber (ADF), neutral detergent fiber (NDF), total carbohydrates (TC) and hemicellulose (HEM). The apparent digestibility coefficient of the nutritive components did not differ when evaluated by the total feces collection. However, when using the LDA as marker there was significant difference to ADF, where the sorghum silage without additive was higher then sorghum silage with Lacto Silo. The sorghum silage with corn meal was similar to other two silages. There was significant correlation only to TC and HEM, between the two methodologies used to estimate.digestibility.